The determination of the first critical load on particulate medium of sandy loam foundation - A.N. Badanin; A.K. Bugrov; A.V. Krotov (Инженерно-строительный журнал, 2012)
The article deals with application problems of the mechanics of particulate media in construction. The main body of the article is devoted the contribution of foreign and Russian scientists to the theory of mechanics of granular environments, first of all, of the author of this theory. A theoretical substantiation of definition of the first critical load on the foundation according to the mechanics of particulate media theory by I.I. Kandaurov is presented. Further comparison of results of full-scale ground tests on a real building site and calculations by the offered theoretical substantiation is executed. The comparison results show the possibility of application of the mechanics of particulate media on foundations’ design. At the end of the article the proposal on continuation of research in this direction and revival of the domestic school of the I.I. Kandaurov theory of particulate media is stated.